2016
DOI: 10.1056/nejmsa1600011
|View full text |Cite
|
Sign up to set email alerts
|

Public-Access Defibrillation and Out-of-Hospital Cardiac Arrest in Japan

Abstract: In Japan, increased use of public-access defibrillation by bystanders was associated with an increase in the number of survivors with a favorable neurologic outcome after out-of-hospital ventricular-fibrillation cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
204
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 254 publications
(213 citation statements)
references
References 36 publications
5
204
0
4
Order By: Relevance
“…The All‐Japan Utstein Registry of the FDMA, a nationwide prospective, population‐ and Utstein‐based registry, enabled us to evaluate the effectiveness of continuous chest compressions and defibrillation by lay‐rescuers5 and the importance of continuously improving the chain of survival at the population level 11. In the JAAM‐OHCA Registry, the special committee has systemically merged in‐hospital databases and the All‐Japan Utstein Registry database by focusing on the use of key items in all data sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The All‐Japan Utstein Registry of the FDMA, a nationwide prospective, population‐ and Utstein‐based registry, enabled us to evaluate the effectiveness of continuous chest compressions and defibrillation by lay‐rescuers5 and the importance of continuously improving the chain of survival at the population level 11. In the JAAM‐OHCA Registry, the special committee has systemically merged in‐hospital databases and the All‐Japan Utstein Registry database by focusing on the use of key items in all data sources.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the registry were previously described 2, 5. Data were collected prospectively using the data form of the Utstein‐style international guideline for reporting OHCA 9.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of public‐access AEDs has rapidly increased, with >360 000 devices located throughout Japan in 2012 (including 25 000 in Osaka Prefecture) 9. Previous studies suggested that the nationwide dissemination of public‐access AEDs allowed early defibrillation by bystanders, leading to increased survival rates after OHCA 10, 11. Nevertheless, in the era of the public‐access defibrillation (PAD), we identified no published studies of the long‐term effects of bystander CPR and public‐access AED on the outcome of exercise‐related OHCA.…”
Section: Introductionmentioning
confidence: 92%
“…With the full cohort, 3 generalized estimating equation models (univariate, adjusted for selected variables, and adjusted for all covariates) were fit using each of the 3 end points as a dependent variable. A set of potential confounders was chosen a priori based on biological plausibility and a priori knowledge 12, 15, 24, 30, 31, 32, 33, 34, 35, 36, 37, 38. These selected variables included the following: age, sex, hospital category (to adjust for the difference in the frequency of mCPR device use between each institution, hospitals were categorized on the basis of the numbers of patients on whom mCPR devices were used: low volume, <20 per year; moderate volume, 20–100 per year; and high volume, >100 per year), witnessed status, bystander CPR, first documented rhythm, presumed cardiac cause, airway management by EMS, prehospital administration of epinephrine by EMS, tracheal intubation during advanced cardiovascular life support, administration of epinephrine, defibrillation attempt, extracorporeal CPR performed in the ED, and time from call to EMS arrival at scene, time from EMS arrival at scene to EMS arrival at the patient's side, time from EMS arrival at the patient's side to CPR initiation, and time from CPR initiation to hospital arrival (while also adjusting for within‐institution clustering effects using a generalized estimating equation,36, 37, 38, 39 because several articles have suggested the existence of hospital‐related differences in survival after OHCA) 40, 41, 42, 43, 44.…”
Section: Methodsmentioning
confidence: 99%